Les représentations de la bataille de La Nouvelle-Orléans - Pierre-François PEIRANO (E-REA)
A landmark event in the military history of the United States, the battle of New Orleans, fought on January 8th, 1815, accounted for the strategic role still played by the city in the early 19th century. The victory of American Arms was instrumental in establishing the legend of General Andrew Jackson. Throughout the decades, the battle was commemorated on multiple occasions and this article will focus on the most striking paintings and engravings of the event that will be chronologically examined. However, the analysis will also include other means to relate, popularize and celebrate it, so as to draw up a “mental image” of the battle, so to speak, as well as to analyze its importance in the identity and the history of New Orleans, even the history of the United States.